The influence of lanthanum content in the Fe2O3-Li2O-La(OH)3 system on phase formation and properties of composite material; Тонкие химические технологии; Vol 20, No 2 - Elkina Yuliya Sergeevna Yu. S.; Vlasov V. A. Vitaliy Anatolievich; Lysenko E. N. Elena Nikolaevna; Surzhikov A. P. Anatoly Petrovich (2025, 2025)
Title screen